Novel scheduling algorithm for optimizing real-time multimedia performance in Long-Term Evolution Advanced - Mohd. Ramli, Huda Adibah; Rizman, Zairi Ismael (Scientific and Technological Research Council of Turkey, 2017)
Real-time multimedia applications are becoming increasingly popular among mobile cellular users. Given that Long Term Evolution-Advanced (LTE-A) which is an emerging mobile cellular standard needs to support these multimedia applications, packet scheduling is of paramount importance in LTE-A. This paper proposes a packet scheduling algorithm known as Novel Scheduling for usage in the downlink LTE-A. It takes channel quality, average throughput and packet delay into account when determining priority of each user. Simulation results demonstrated the efficacy of the proposed algorithm in optimizing real-time multimedia performance for more mobile cellular users.